Sistem Informasi Logistik Non Medis pada Rumah Sakit Bhayangkara Palembang - Mulyana, Yana; RC, John; Aryati, Nining; Sanmarino, A (Jurnal Sistem Informasi dan Teknik Informatika (JAFOTIK), 2023)
Bhayangkara Palembang Hospital is a hospital classified as a Level III Bhayangkara Hospital, which is at least capable of providing health services in the form of eleven basic specialists in providing non-medical logistical needs. The system used by Bhayangkara Palembang Hospital is still very limited, starting from submitting non-medical logistics needs from each section, approval of the procurement of non-medical logistics needs by the leadership, and managing non-medical logistics data by the admin section. With the non-medical logistics procurement system that is currently running, Bhayangkara Palembang Hospital requires more time because the request to procurement process has to go through a fairly long process. This will affect the quality of service at Bhayangkara Hospital in Palembang because non-medical logistics supplies cannot be fulfilled quickly before old supplies run out. Therefore, to improve the quality of service at Bhayangkara Palembang Hospital, especially in the procurement of non-medical logistics, changes are needed to the current system by implementing the non-medical logistics information system at Bhayangkara Palembang Hospital so that it can simplify and speed up the process of submission, approval, data management, and procurement of non-medical logistics.